Dynamics of Subjective Well-Being in Early Marriage: A Phenomenological Review of Madurese Women - Yudho Bawono; Dewi Retno Suminar; Wiwin Hendriani (Universitas Islam Tribakti Lirboyo Kediri, 2022)
The study aims to theoretically explain the dynamics of subjective well-being in the early marriage of Madurese women. This study used a qualitative research method with an Interpretative Phenomenological Analysis (IPA) approach. The data collection used the semi-structured interview with the interview guide containing questions that reflect the ephocÄ“. The participants in this study were 9 Madurese women who lived in Bangkalan Regency, Sampang Regency, Pamekasan Regency, and Sumenep Regency. There were important points that became the findings of this study, including (a) Madurese women who married early could achieve subjective well-being proven with statements that indicated life satisfaction in their marriage and could feel positive emotions more often than negative emotions, and (b) The achievement of subjective well-being of Madurese women who married early could not be separated from their husband's acceptance and support.